Culture, parenting, and language: Respeto in Latine mother–child interactions. Issue 3 (30th December 2019) - Tamis‐LeMonda, Catherine S.; Caughy, Margaret O'Brien; Rojas, Raúl; Bakeman, Roger; Adamson, Lauren B.; Pacheco, Daniel; Owen, Margaret Tresch; Suma, Katharine; Pace, Amy
Abstract: The cultural value of respeto (respect) is central to Latine parenting. Yet, how respeto manifests in the interactions of Latine parents and their young children remains unexamined. Low‐income Mexican immigrant Spanish‐speaking mothers and their 2.5‐year‐old toddlers ( N = 128) were video‐recorded during play ( Mage = 30.2 months, SD = 0.52), and two culturally informed items of respeto were coded: parent calm authority and child affiliative obedience. Respeto related to standard ratings of mother and child interactions (e.g., maternal sensitivity and child engagement) but also captured unique features of parent–child interactions. Respeto related to mothers' and toddlers' language production and discourse during the interaction, and explained unique variance in language variables above standard ratings of mother–child interaction. This is the first effort to document a culturally salient aspect of dyadic interaction in Mexican immigrant mothers and young children and to show that respeto relates to language use during mother–child interactions.